2002
DOI: 10.1007/s10067-002-8273-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Radiographic Knee Osteoarthritis in Saudi Arabia

Abstract: In this cross-sectional study we looked at the radiographic evidence of osteoarthritis (OA) of the knee in 300 randomly chosen patients attending 14 primary care facilities for different medical conditions. Radiographic OA was seen in 89 out of 167 males (53.3%) and in 81 out of 133 females (60.9%). The patella was involved with radiographic osteoarthritic changes in 80.7% and 87.8% of female and male OA patients, respectively. In most cases the medial compartment joint space was narrowed. Radiographic OA of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 4 publications
1
33
0
Order By: Relevance
“…Previous study reported that approximately 60.9% female and 53.3% male adults aged 30–93 years had shown radiographic evidence of knee OA in the Middle East [4]. Another study reported the prevalence of knee OA in the Saudi Arabia was around 30.8% in the adult aged 46–55 years and 60.6% in the adult aged 66–75 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported that approximately 60.9% female and 53.3% male adults aged 30–93 years had shown radiographic evidence of knee OA in the Middle East [4]. Another study reported the prevalence of knee OA in the Saudi Arabia was around 30.8% in the adult aged 46–55 years and 60.6% in the adult aged 66–75 years [5].…”
Section: Introductionmentioning
confidence: 99%
“…In Asian studies of symptomatic OA knee, radiological methods have often been inconsistent and unclear and the degree of abnormality in individual compartments has been difficult to ascertain. When specifically explored the patellofemoral joint (PFJ) was found to be significantly involved, as shown by Al‐Arfaz, who found PFJ in > 80% of patients with knee OA in Saudi Arabia 23 . However, he reported that medial tibiofemoral joint (MTFJ) abnormality predominated in the Saudi hospital; this was also reported from Kuwait, 18 but it is unclear if lateral or skyline views were taken.…”
Section: Introduction and Reviewmentioning
confidence: 97%
“…Many literatures mentioned medial compartment is more commonly involved than the lateral one and the pathogenesis may be different [1][2][3][4][5][6][7]. In 2006, it was reported that in patients with medial compartment osteoarthritic knees, the prevalence of medial plica was significantly higher than that of others and that two distinct foci of cartilaginous lesion were found on the facing medial femoral condyle in almost all of the patients who had the structure of medial plica [8].…”
Section: Introductionmentioning
confidence: 98%